2013
DOI: 10.1016/j.jpeds.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Primary Care Provider Practices, Knowledge, and Attitudes of Human Immunodeficiency Virus Screening among Adolescents

Abstract: Objectives To evaluate pediatric primary care provider (PCP) HIV screening practices, knowledge, and attitudes. Study design Anonymous cross-sectional, internet-based survey of pediatric PCPs from 29 primary care practices. Survey items assessed current HIV screening practices and knowledge, attitudes, and perceived barriers towards screening. Provider demographics and practice characteristics were analyzed for associations with screening through logistic regression. Results Of 190 PCPs, there were 101 eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
1
27
1
Order By: Relevance
“…Primary healthcare may be viewed by some as optional, except in cases of urgent medical need, due to the high expense of quality medical care combined with the expense of taking time from work for visits [45]. However, while further research is needed that focuses on the relationship between resources available to BMSM and their use of services, access to general healthcare services does not necessarily yield receipt of HIV testing and prevention services [46, 47]. One study among BMSM found a positive association between having health insurance and being unaware of one's HIV-positive status, suggesting that other factors such as stigma, fear of diagnosis, and perceived quality of services may serve more significant roles as barriers to learning one's status [48] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Primary healthcare may be viewed by some as optional, except in cases of urgent medical need, due to the high expense of quality medical care combined with the expense of taking time from work for visits [45]. However, while further research is needed that focuses on the relationship between resources available to BMSM and their use of services, access to general healthcare services does not necessarily yield receipt of HIV testing and prevention services [46, 47]. One study among BMSM found a positive association between having health insurance and being unaware of one's HIV-positive status, suggesting that other factors such as stigma, fear of diagnosis, and perceived quality of services may serve more significant roles as barriers to learning one's status [48] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…3 Adolescents receiving this diagnosis in the ED are unlikely to have received adequate counseling regarding safer sexual practices, which is important given that repeated episodes of PID increase the risk of chronic pelvic pain and infertility, further increasing the importance of this follow-up appointment. 1,4,5 There were a myriad of reasons given for not attending a follow-up appointment including inadequate PCP availability, symptom improvement, and lack of understanding of importance of follow-up. The varied reasons for not following up are similar to other studies examining post-ED follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…3 This follow-up appointment is particularly important for adolescents who commonly receive the diagnosis of PID in emergency departments (ED) or urgent care centers where time constraints result in limited counseling at the time of diagnosis. 4,5 Unfortunately, with follow-up rates as low as 10–16%, the majority of adolescents diagnosed with PID are not receiving the recommended follow-up care, which likely contributes to the high rates of long-term complications. 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…11,13,14 In contrast, pediatricians seem to be the least likely to routinely offer HIV testing to their patients and tend to view testing for HIV as a lower priority than other adolescent issues, such as sexually transmitted infections, violence, or substance abuse. 16,17 Researchers have found that female physicians seem more willing to adopt routine HIV testing practices, 7,8,11,16,17 as are younger practitioners 11,17 and those who completed training within the past 10 years. 16 The adoption of routine HIV testing has also been found to be related to whether a physician has diagnosed patients with HIV in the past year.…”
Section: Introductionmentioning
confidence: 99%